A performance versus cost analysis of prepreg carbon fibre epoxy energy absorption structures. (June 2015) - Meredith, James; Bilson, Edward; Powe, Richard; Collings, Ed; Kirwan, Kerry
Abstract: Carbon fibre epoxy composites are sought after for their excellent specific energy absorption (SEA) but are costly. A range of prepreg carbon fibre epoxy layups were subjected to a 10 m/s impact with 4 kJ of energy. Fibre volume fraction and voidage were determined for each sample and the fracture analysed in detail. SEA ranged from 35.27 J/g to 60.25 J/g with the highest performance from 8 plies of 200 gsm 2 × 2 twill all laid at 0°. Vacuum assisted oven cure resulted in higher voidage than autoclave cure (2.52% versus 0.17%) but did not affect SEA. According to a ratio of performance to cost the highest rated samples were an 8 ply oven cure and a 3 ply autoclave cure specimen and there was little difference between them. This work has highlighted that there is enormous potential for cost reduction of prepreg carbon fibre epoxy energy absorption structures through the use of heavier areal weight fabrics and fewer plies as well as through the use of oven cured prepreg.